Nitrogen removal by a combined subsurface vertical down-flow and up-flow constructed wetland system - Suwasa Kantawanichkul (2018)
A subsurface vertical up-flow followed by down-flow constructed wetland system was used to treat anaerobic digester effluent from pig-farm wastewater. The system consists of two beds connected in series and have equal size of 1.2 × 1.2 × 0.6 m (W × L × D). The first bed was planted with Typha angustifolia and the second bed was planted with Cyperus alternifolius L. The wastewater with NH 3 -N and chemical oxygen demand (COD) concentration of approximately 300 mg l -1 was fed to the first bed which performed as a vertical up-flow bed and then passed to the second vertical down-flow bed and recirculated to the first bed with the recycle ratio of 1:1 to enhance nitrogen removal. The system was operated with the hydraulic loading rate (HLR) of 10, 20, 30 and 40 cm day -1 including recycled water to evaluate the capability of the system under high HLR. The results showed that the removal efficiencies of N and COD decreased when the system operated with higher HLR. The removal efficiency for NH 3 -N and COD was maximum at 10 cm day -1 (79 and 74% respectively). Nitrification was significant in vertical down-flow bed, denitrification in the up-flow bed at every HLR. The two-stage constructed wetland removed 96-98% of incoming total suspended solids (TSS) and the removal was not affected by high HLR. The removal efficiency of total phosphorus (TP) was low (24-27%) at all HLR. © 2008 Springer Netherlands.